1996
DOI: 10.1128/mcb.16.5.2083
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of IκBβ by the Tax Protein of Human T-Cell Leukemia Virus Type 1: a Potential Mechanism for Constitutive Induction of NF-κB

Abstract: In resting T lymphocytes, the transcription factor NF-B isHuman T-cell leukemia virus type 1 (HTLV-1) is the causative agent of adult T-cell leukemia, an aggressive and often fatal malignancy of activated CD4 ϩ T lymphocytes (54, 82). This oncogenic retrovirus encodes a 40-kDa protein, termed Tax, which appears to play a central role in the process of neoplastic transformation (31,50,55,69,75). In this regard, Tax has the capacity to constitutively activate members of the NF-B/Rel family of transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
160
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(168 citation statements)
references
References 79 publications
8
160
0
Order By: Relevance
“…4). Indeed, co-transfection studies by McKinsey et al have shown that I B-␤ over-expression can directly inhibit RelA transactivation of a heterologous promoter containing HIV-1 B enhancer cassette [57]. Finally, we have shown that the induction of mRNA expression of a second chemokine, monocyte chemotactic protein-1 (MCP-1), by IL-1␤ in Caco-2 cells is also inhibited by sodium butyrate in a dose-dependent fashion [12].…”
Section: Discussionmentioning
confidence: 61%
“…4). Indeed, co-transfection studies by McKinsey et al have shown that I B-␤ over-expression can directly inhibit RelA transactivation of a heterologous promoter containing HIV-1 B enhancer cassette [57]. Finally, we have shown that the induction of mRNA expression of a second chemokine, monocyte chemotactic protein-1 (MCP-1), by IL-1␤ in Caco-2 cells is also inhibited by sodium butyrate in a dose-dependent fashion [12].…”
Section: Discussionmentioning
confidence: 61%
“…Speci®city of the antibody to p300 was con®rmed by the absence of Tax in the immunoprecipitate when p300 was incubated with Luciferase protein (Luciferase) or when Tax protein was incubated in the absence of p300 (control). proteins such as IkBa and IkBb to the ubiquitinproteasome degradation pathway (Brockman et al, 1995;McKinsey et al, 1996). However, c-Myb expression was not signi®cantly a ected when CMVc-Myb and CMV Tax were co-expressed in transient transfection assays (Figure 5b), suggesting that Tax suppression of c-Myb transactivation potential and the consequent repression of the c-Myb promoter are not direct consequences of a decrease in c-Myb at the protein level.…”
Section: Repression Of the C-myb Promoter By The Tax Protein Through mentioning
confidence: 96%
“…Of the factors targeted by Tax, NFkB clearly plays a prominent role in deregulation of cellular gene expression. Tax induces the nuclear expression of members of the NFkB family of transcription factors, which leads to expression of many gene promoters containing NFkB motifs (Lacoste et al, 1991;Lindholm et al, 1991;Li et al, 1993;Kanno et al, 1994;Brockman et al, 1995;Maggirwar et al, 1995;McKinsey et al, 1996). These genes include those encoding interleukin-2 (IL-2), IL-2 receptor a (IL2Ra), IL-3, GM-CSF, as well as HIV-1 (Siekevitz et al, 1987;Ballard et al, 1988;Leung and Nabel, 1988;Wano et al, 1988;Bo¨hnlein et al, 1989;Nimer, 1991).…”
Section: Role Of Tax In Htlv Pathogenesismentioning
confidence: 99%